2000
DOI: 10.2166/wst.2000.0389
|View full text |Cite
|
Sign up to set email alerts
|

The genotoxity of by-products by chlorination and ozonation of the river water in the presence of bromide ions

Abstract: This study focused on the evaluation of the genotoxic characteristics of chlorinated and brominated substances produced by ozonation and chlorination of the river waters containing bromide ions. The mutagenic activities of drinking waters and disinfected river waters were measured by Ames tests using S. typhimurium strains TA100 and TA98, and by chromosomal aberration test using cultured Chinese hamster lung cells (CHL/IU) in vitro. After flowing samples through CSP800 or XAD-2 resin column, absorbed substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Recent epidemiological studies reported that brominated DBPs are more carcinogenic than their chlorinated analogs [17][18][19][20]. A recent study conducted in Istanbul showed that the lifetime cancer risk of THMs was highest in the Esenyurt district of Buyukcekmece water distribution system in Istanbul, and, dibromochloromethane (DBCM) contributed a higher cancer risk to Istanbul residents through a dermal route than did the other three THM compounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological studies reported that brominated DBPs are more carcinogenic than their chlorinated analogs [17][18][19][20]. A recent study conducted in Istanbul showed that the lifetime cancer risk of THMs was highest in the Esenyurt district of Buyukcekmece water distribution system in Istanbul, and, dibromochloromethane (DBCM) contributed a higher cancer risk to Istanbul residents through a dermal route than did the other three THM compounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, by-products of disinfection, such as trihalomethanes (THMs) and other hazardous compounds, produced in the chlorination of raw water in purification plants, are contained in drinking water (Meier 1988;Nobukawa and Sanukida 2000). The formation potential of these disinfection by-products in purification plants is dependent on the amount of organic material in the raw water (Rook 1974;Kito and Nakanishi 1987;Nakamuro et al 1989;Vartinen and Limatainen 1998;Nobukawa and Sanukida 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, HOBr can react quickly with NOM to form brominated disinfection byproducts (Br-DBPs) (Cowman and Singer, 1996;Richardson et al, 2003;Zhao et al, 2012;Pan and Zhang, 2013), which are more carcinogenic than their chlorinated analogues (Nobukawa and Sanukida, 2000). Because copper ions can inactivate certain bacterial species (Feng et al, 1996), copper has been extensively used in water distribution pipes throughout the world.…”
mentioning
confidence: 99%